(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Some people claim that the death of the author is a twentieth-century issue. They think that it was initiated for the first time by Roland Barthes in 1968 and consolidated by M. Foucault and others. The objective is to manipulate this information as a justification for establishing a radical discontinuity between Modern Literary Theory and Traditional Criticism. This assumption, however, does not stand to reason. The critical establishment has always maintained that literary ubiquity is possible only through the authorial anonymity. In “Tradition and the Individual Talent”, T.S. Eliot demonstrates in detail that the man of letters is a mere catalyst and that impersonality is the differentia specifica of literariness. Similarly, Wimsatt and Beardsley reiterate, in “The Intentional Fallacy”, that any form of attention devoted to the author can be anything such as biography or psychology, but it can never be literary criticism. All the elements needed by the work of art are already in it. The symmetrical similarities between the traditional and the modern positions establish the fact that the death of the author is one of the continuities, past and present, in the literary institution. يعتقد البعض أن مفهوم موت المؤلف قضية نقدية خاصة بالقرن العشرين وأنها بدأت مع رولاند بارت وتعمقت مع ميشيل فوكو. إن الغاية من هذا المنظور خلق قطيعة جذرية بين نظرية الأدب الحديثة والنقد الأدبي التقليدي. ولكن حقائق المؤسسة النقدي تدحض هذا التصنيف وتؤكد أن "موت المؤلف"، كغيره من منظومة المصطلحات الحديثة، له تاريخ طويل. لقد أكد أعلام النقد التقليدي أن انتشار الأدب وعالميته يشترطان موت المؤلف. ففي "التراث والموهبة الفردية"، يبرهن ت.س. إليوت على أن الأديب العظيم وسيط حيادي وأن الموضوعية أو اللاذاتية تشكلان ماهية الهوية الأدبية. وفي "المغالطة القصدية"، يؤكد الناقدان ويمزات وبيردزلي أن الدراسات التي تتناول المؤلف تنتمي إلى السيرة الذاتية أو التحليل النفسي ولكنها لا يمكن أن تكون نقدا أدبيا. ويضيفان أن العناصر الضرورية للعمل الإبداعي مودعة وموجودة داخل النص ذاته. هذه القواسم المشتركة بين النقد التقليدي ونظرية الأدب الحديثة براهين نسقية وثائقية خلاصتها أن موت المؤلف هو واحدة ثوابت المؤسسة الأدبية منذ البدايات الأولى.